2020
DOI: 10.1111/avsc.12498
|View full text |Cite
|
Sign up to set email alerts
|

Native parasitic plants: Biological control for plant invasions?

Abstract: Plant invasions cause biodiversity loss and degradation in ecosystems worldwide. The invasive species involved may be introduced, or native invaders, and controlling them is a major global challenge. Here, we highlight an emerging role for native parasitic plants in suppressing invasive species, thus aiding in restoration of affected habitats. Compelling empirical evidence is provided by three study systems located in Central Europe, southern Australia and eastern China. Further cases of parasitism of invasive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…We also found that the water and nitrogen status of the parasite was higher in well watered conditions, suggesting that it was better able to extract resources under these conditions; this may explain why its impact on host shoot biomass and S : R was greater in high water. Our data continue to support the potential use of some native hemiparasites as biocontrols for major invasive shrubby weeds (Tĕšitel et al ., 2020) and suggest that parasite impact is likely to be greater in higher rainfall areas, regardless of soil nitrogen conditions. However, as some regions become drier and warmer in the future (Klausmeyer & Shaw, 2009), we may expect the impact of hemiparasitic plants on host performance to decline.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that the water and nitrogen status of the parasite was higher in well watered conditions, suggesting that it was better able to extract resources under these conditions; this may explain why its impact on host shoot biomass and S : R was greater in high water. Our data continue to support the potential use of some native hemiparasites as biocontrols for major invasive shrubby weeds (Tĕšitel et al ., 2020) and suggest that parasite impact is likely to be greater in higher rainfall areas, regardless of soil nitrogen conditions. However, as some regions become drier and warmer in the future (Klausmeyer & Shaw, 2009), we may expect the impact of hemiparasitic plants on host performance to decline.…”
Section: Resultsmentioning
confidence: 99%
“…They are an important group because of their direct and indirect impacts on ecosystems, communities and individual species across their global distribution (Press & Phoenix, 2005). For example, parasitic plants can increase nutrient cycling or affect plant community structure and diversity via their impacts at the host population level (Bardgett et al ., 2006; Quested, 2008; Hartley et al ., 2015; Tĕšitel et al ., 2020). Numerous studies have investigated parasitic plant effects on their hosts (Press & Graves, 1995; Watling & Press, 2001; Press & Phoenix, 2005; Bell & Adams, 2011), but few studies have investigated the impact of multiple environmental factors on these associations (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Parasitism and clonal integration each have strong community‐level effects on their own. For example, through differential effects on hosts and nonhosts and by decreasing the density of vegetation, parasitic plants can change plant community structure (Press & Phoenix, 2005), promote plant species diversity (Grewell, 2008; Heer et al ., 2018), and control invasive plant species (Shen et al ., 2007; Yu et al ., 2008; Cirocco et al ., 2017; Tĕšitel et al ., 2017, 2020; Li et al ., 2019). Clonal integration may modify the response of plants to grazing (Liu et al ., 2020) and help explain why increased dominance by tall, wide‐spreading clonal plants accounts for much of the negative effects of elevated N levels on diversity in some grasslands (Gough et al ., 2012; Dickson et al ., 2014), and why clonal growth in plants is associated with invasiveness (Pyšek et al ., 1995; Pyšek, 1997; Liu et al ., 2006; Song et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Těšitel et al . (2020), in a Forum article, discussed the role of native parasitic plants, especially root hemiparasites, mistletoes and parasitic vines, in suppressing native and alien invaders. They provide examples from different continents how these species can reduce the spread of invaders, and call for more widespread use of native parasitic plants as biological control agents.…”
Section: Editors’ Award For 2020mentioning
confidence: 99%